2023
DOI: 10.1186/s13018-023-04153-1
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum 4-Hydroxynonenal level as a biomarker for the progression of steroid-induced osteonecrosis of the femoral head

Fangjun Xiao,
Tengfei Wei,
Huan Xiao
et al.

Abstract: Background Osteonecrosis of the femoral head (ONFH) is becoming a prevalent global health problem. 4-Hydroxynonenal (4-HNE) serves as a common marker of oxidative stress. This study aims to study the potential role of 4-HNE in the progression of steroid-induced osteonecrosis of the femoral head (SIONFH). Method Between April 2021 and December 2021, 64 subjects were enrolled in this cross-sectional case‒control study. Thirty-six patients were groupe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In the past decade, many studies have focused on identifying susceptible sites of ONFH [6][7][8]. With the continuous development of high-throughput sequencing technology, extensive research on the gene expression products of ONFH has identified thousands of differentially expressed genes, many of which can serve as biomarkers for early diagnosis and molecular targeted treatment [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, many studies have focused on identifying susceptible sites of ONFH [6][7][8]. With the continuous development of high-throughput sequencing technology, extensive research on the gene expression products of ONFH has identified thousands of differentially expressed genes, many of which can serve as biomarkers for early diagnosis and molecular targeted treatment [9,10].…”
Section: Introductionmentioning
confidence: 99%